0061 Epidemiological study of lung inflammation and oxidative damage in indium tin oxide workers. (23rd June 2014) - Wu, Wei-Te; Chung, Yu-Teh; Liao, Hui-Yi; Lai, Ching-Huang; Chen, Chang-Yuh; Lee, Lien-Hsiung; Chen, Chiou-Jong; Liou, Saou-Hsing
Abstract : Objectives: Indium Tin Oxide (ITO) is widely used in many kinds of touch panels nowadays. Workers could expose to ITO particles from sintering granules, splashing, pulverisation, cutting, and grinding processes. This study aimed to assess the relationship between ITO exposure and lung inflammation and oxidative damage in ITO workers. Method: We recruited 148 exposed workers and 38 control workers from ITO powder process, recycling and ITO target manufacturing plants in Taiwan. Indium in serum (S-In) and urine (U-In) was determined as biomarkers of exposure. Exposed group was further divided as high (S-In > 3 µg/L and low exposed groups (S-In £3 µg/L). Urinary and plasma 8-hydroxy-2-deoxyguanosine (8-OHdG), serum Clara cell protein (CC16), and fractional exhaled nitric oxide (FENO) were measured as biomarkers of oxidative damage and pulmonary inflammation, respectively. Results: The geometric mean air concentrations of indium were 0.0041 ± 2.49 mg/m 3 by area sampling and 0.017 ± 5.20 mg/m 3 by personal sampling. The mean S-In level and U-In level in high exposed group were 8.01 ppb and 3.45 ppb, respectively. The mean levels of S-In and U-In in high exposed group were significantly higher than those of low exposed group. The mean levels of serum CC16 and urinary 8-OHdG in high exposed group were also significantly higher than those of low exposed groups. After adjusting potential confounders, dose-response gradients were found between S-In and CC16 (p = 0.020) and between S-In and urinary 8-OHdG (p = 0.027), respectively. Conclusions: We concluded that indium particles exposure may induce lung inflammation and DNA oxidative damage.